2020
DOI: 10.1155/2020/8894471
|View full text |Cite
|
Sign up to set email alerts
|

The Alveolar Ridge Splitting Technique on Maxillae: A Biomechanical Human Cadaveric Investigation

Abstract: The alveolar ridge splitting technique (ARST) offers an alternative to classic ridge augmentation techniques for successful insertion of dental implants. However, the buccal lamella is at risk of fracturing during ARST distraction. To better understand the fracture mechanisms and displacement limits of the split lamella, this study conducted biomechanical tests on human cadaveric maxilla specimens having extremely atrophied alveolar ridges treated with ARST. A total of 12 standardized alveolar splits were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The fracture force showed a nonlinear correlation with the height of the bone lamella. A similar finite element analysis was carried out in three human frozen maxillas from elderly cadavers 51 . That small study sample showed a mean split stiffness at 27.4 N/mm and a significant correlation between stiffness and failure force (seen as a significant drop in the reaction force during testing).…”
Section: Experimental Studiesmentioning
confidence: 90%
“…The fracture force showed a nonlinear correlation with the height of the bone lamella. A similar finite element analysis was carried out in three human frozen maxillas from elderly cadavers 51 . That small study sample showed a mean split stiffness at 27.4 N/mm and a significant correlation between stiffness and failure force (seen as a significant drop in the reaction force during testing).…”
Section: Experimental Studiesmentioning
confidence: 90%